Differential Activation of Glioprotective Intracellular Signaling Pathways in Primary Optic Nerve Head Astrocytes after Treatment with Different Classes of Antioxidants - Anita K. Ghosh; Vidhya R. Rao; Victoria J. Wisniewski; Alexandra D. Zigrossi; Jamie Floss; Peter Koulen; Evan B Stubbs; Simon Kaja (MDPI AG, 2020)
Optic nerve head astrocytes are the specialized glia cells that provide structural and trophic support to the optic nerve head. In response to cellular injury, optic nerve head astrocytes undergo reactive astrocytosis, the process of cellular activation associated with cytoskeletal remodeling, increases in the rate of proliferation and motility, and the generation of Reactive Oxygen Species. Antioxidant intervention has previously been proposed as a therapeutic approach for glaucomatous optic neuropathy, however, little is known regarding the response of optic nerve head astrocytes to antioxidants under physiological versus pathological conditions. The goal of this study was to determine the effects of three different antioxidants, manganese (III) tetrakis (1-methyl-4-pyridyl) porphyrin (Mn-TM-2-PyP), resveratrol and xanthohumol in primary optic nerve head astrocytes. Effects on the expression of the master regulator nuclear factor erythroid 2-related factor 2 (Nrf2), the antioxidant enzyme, manganese-dependent superoxide dismutase 2 (SOD2), and the pro-oxidant enzyme, nicotinamide adenine dinucleotide phosphate oxidase 4 (NOX4), were determined by quantitative immunoblotting. Furthermore, efficacy in preventing chemically and reactive astrocytosis-induced increases in cellular oxidative stress was quantified using cell viability assays. The results were compared to the effects of the prototypic antioxidant, Trolox. Antioxidants elicited highly differential changes in the expression levels of Nrf2, SOD2, and NOX4. Notably, Mn-TM-2-PyP increased SOD2 expression eight-fold, while resveratrol increased Nrf2 expression three-fold. In contrast, xanthohumol exerted no statistically significant changes in expression levels. 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) uptake and lactate dehydrogenase (LDH) release assays were performed to assess cell viability after chemically and reactive astrocytosis-induced oxidative stress. Mn-TM-2-PyP exerted the most potent glioprotection by fully preventing the loss of cell viability, whereas resveratrol and xanthohumol partially restored cell viability. Our data provide the first evidence for a well-developed antioxidant defense system in optic nerve head astrocytes, which can be pharmacologically targeted by different classes of antioxidants.